2022
DOI: 10.15587/1729-4061.2022.255331
|View full text |Cite
|
Sign up to set email alerts
|

Improving the property of wear rate and hardness by adding hybrid nanomaterials to AA7075

Abstract: Aluminum alloys have become an essential material in many modern applications, such as automobiles, marines and aviation industries. It is expected that more applications will heavily depend on aluminum alloys to reduce the weight and maintain safety standards, many previous studies have done in this regard. Numerous of these applications’ parts could be subjected to different loading and environmental conditions. This includes wearing stress and loss of the surface properties. To address these issues, intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The experiment's findings indicated that adding alumina nanoparticles improved the composite alloy's hardness and tensile strength before the weight ratio reached 6 %, the research used restrictive size nanoparticle in all experiments. Wear improved by [17] using hybrid nanoparticle additive to the aluminum alloy. As the proportion of hybrid Nano-reinforced materials is increased, the produced composites' hardness (BH) rises.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The experiment's findings indicated that adding alumina nanoparticles improved the composite alloy's hardness and tensile strength before the weight ratio reached 6 %, the research used restrictive size nanoparticle in all experiments. Wear improved by [17] using hybrid nanoparticle additive to the aluminum alloy. As the proportion of hybrid Nano-reinforced materials is increased, the produced composites' hardness (BH) rises.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%